EF STUDENTS’ MOTIVATION IN BLENDED LEARNING ENVIRONMENT (A QUALITATIVE STUDY AT SMPN 29 BENGKULU TENGAH) - Eka Saputri, Reza; Riswanto, Riswanto; Martina, Feny (Yayasan Darussalam Bengkulu, 2022)
The purpose of this study is to find out how student learning behavior is viewed from the aspect of motivation and attention in learning EFL in Blended learning. To find out the obstacles or difficulties faced by students while learning English as a foreign language using blended learning. This research use desciptive qualitative approach. The technique used in data collection is the technique of observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions/verification. Test the validity of the data using triangulation techniques. The results of this study indicate that student learning behavior in terms of motivation and attention in learning English as a foreign language using blended learning has fulfilled the markers of experts employed in theory, however not 100% of students are motivated in blended learning. This is due to a variety of reasons, including signal and quota constraint.